2022
DOI: 10.1007/s40544-021-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance of iron- and nickel-base self-lubricating claddings containing metal sulfides at high temperature

Abstract: Iron-based coatings with the incorporation of solid lubricants have been prepared by means of laser cladding, in an effort to control friction and decrease tool wear at high temperatures during metal forming applications. The choice of a Fe-based powder has been considered advantageous, as it can lead to decreased costs compared to nickel-based claddings previously studied by the authors, in addition to having a lower environmental impact. In particular, the incorporation of transition metal dichalcogenides su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Thereafter, they aroused great concern from researchers at home and abroad. Research has proved that RHEAs have excellent mechanical properties at high temperatures, even surpassing the widely used nickel-based alloy [2][3][4][5][6]. RHEAs, with excellent mechanical properties at elevated temperatures, are considered promising high-temperature application materials, which are suitable for complex working conditions such as atomic energy, aerospace, the military industry, advanced nuclear reactors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, they aroused great concern from researchers at home and abroad. Research has proved that RHEAs have excellent mechanical properties at high temperatures, even surpassing the widely used nickel-based alloy [2][3][4][5][6]. RHEAs, with excellent mechanical properties at elevated temperatures, are considered promising high-temperature application materials, which are suitable for complex working conditions such as atomic energy, aerospace, the military industry, advanced nuclear reactors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the temperature rose to 600 • C, the COF of the three sulfide-added coatings began to fluctuate sharply and the amount of wear increased greatly. This indicates that it is difficult for Ni 3 S 2 , CuS and Bi 2 S 3 to make an effective improvement in the abrasive resistance of Ni-based coatings at 600 • C. Sulfides are unstable and easily oxidized at high temperatures, particularly above 610 • C when the COF of the coating raises sharply, and are not effective in improving the high temperature wear resistance of nickel-based coatings [52]. The authors concluded that the encapsulation on the surface of sulfide by chemical plating proposed by Liu [53] can effectively inhibit its decomposition but also can boost the compatibility with the substrate.…”
Section: Lamellar Solidsmentioning
confidence: 99%